Accident Compensation: The Role of Incentives, Consumer Choice and Competition - Evans, Lewis; Quigley, Neil (Victoria University of Wellington Law Review, 2003)
In the 1990s, the insurance aspect, as opposed to the social welfare or more communitarian face of the Accident Compensation was prominent in public debate. In this paper, Professors Evans and Quigley argue that Accident Compensation is indeed more appropriately seen as an insurance scheme. As such they question the appropriateness of state monopoly provision, believing that competition would give both employers and workers greater choice.